2020
DOI: 10.15414/jmbfs.2020.10.1.61-64
|View full text |Cite
|
Sign up to set email alerts
|

Levan Production Potentials From Different Hypersaline Environments in Turkey

Abstract: 12  halophilic strains from different hypersaline environments such as solar salterns in Tuzlagözü (Sivas), Fadlum (Sivas), Kemah (Erzincan), a hypersaline spring water in Pülümür (Tunceli) and a saline lake in Delice (Kırıkkale) belonging to Turkey, were investigated in terms of levan production. After incubation and ethyl alcohol treatment, dialysis process was operated for partial purification.  Levan amounts in our samples after hydrolysis were calculated based on the amount of sugar obtained by acid hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The synthesis of levan by a halophilic bacterium, Halomonas elongata 153B, isolated from a hypersaline environment, was examined in this work. In the study conducted by our group, the abilities of 12 halophilic strains to produce levan were screened and it was shown that the H. elongata 153B used in our study produced the high-yield levan [34].…”
Section: Introductionmentioning
confidence: 97%
“…The synthesis of levan by a halophilic bacterium, Halomonas elongata 153B, isolated from a hypersaline environment, was examined in this work. In the study conducted by our group, the abilities of 12 halophilic strains to produce levan were screened and it was shown that the H. elongata 153B used in our study produced the high-yield levan [34].…”
Section: Introductionmentioning
confidence: 97%
“…Especially through halophilic bacteria, the biopolymer can be produced with high efficiency in non-sterile conditions, and thus production costs can be reduced. 19,20 There has been an increasing trend toward herbal wound care products that include therapeutics such as extracts from medicinal plants, flavonoids, phenolic compounds and terpenoids in order to regenerate cells, ensure tissue integrity in a short time and reduce infections in the wound area. [21][22][23][24] These components are preferred over synthetic drug agents due to their easy availability from nature, low cost, limited side effects, high bioavailability, and efficacy in treatment.…”
Section: Introductionmentioning
confidence: 99%